Space Using of Sumatra Slow Loris (Nycticebus coucang) Release by International Animal Rescue Indonesia (IARI) in Protected Forest Batutegi Kalijernih Tanggamus Lampung - Nora Fery Matondang; Bainah Sari Dewi; Indah Winarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2018)
Nycticebus coucang had the closely related to their habitat. The observation research to determine using of (1) forest stratum, (2) substrate space (3) canopy space (4) vegetation types and (4) daily behavior of N.coucang in Protected Forest KPHL Batutegi Block Kalijernih, Tanggamus Lampung, February-May 2014, used the explore, one zero sampling and rapid assessment methods. The results of the 60 days observation was found 50 hours N.coucang behavior observed for a total of 3652 data, N.coucang used (1) forest floor (57%), understory layer (42,7%), canopy layer (0,2%), (2) A substrate (4,3%), B substrate (13%), C substrate (43,7%), D substrate (38,3%), E substrate (0,4%) and F substrate (0,08%), (3) middle (24,6%), top middle (16,7%), middle down (14,7%), middle edge (20,8%), top edge(13,4%), bottom edge (0,9%), (4) vegetation type are stake (46,2%), pole (33,6%) and tree (20%), (5) to did daily behavior are travelling (56,7%), feeding (7,5%), forage (25,9%), grooming (5,7%), active (3,6%), inactive (0,2%), and defecating (0,02%). Keywords: Selection and space using of forest, Nycticebus coucang, KPHL Batutegi